A nationwide population-based cohort study of peripartum hysterectomy and arterial embolisation in Belgium: results from the Belgian Obstetric Surveillance System. Issue 11 (8th November 2017) - Vandenberghe, Griet; Guisset, Marine; Janssens, Iris; Leeuw, Virginie Van; Roelens, Kristien; Hanssens, Myriam; Russo, Erika; Van Keirsbilck, Joachim; Englert, Yvon; Verstraelen, Hans
Abstract : Objectives: To assess the prevalence of major obstetric haemorrhage managed with peripartum hysterectomy and/or interventional radiology (IR) in Belgium. To describe women characteristics, the circumstances in which the interventions took place, the management of the obstetric haemorrhage, the outcome and additional morbidity of these women. Design: Nationwide population-based prospective cohort study. Setting: Emergency obstetric care. Participation of 97% of maternities covering 98.6% of deliveries in Belgium. Participants: All women who underwent peripartum hysterectomy and/or IR procedures in Belgium between January 2012 and December 2013. Results: We obtained data on 166 women who underwent peripartum hysterectomy (n=84) and/or IR procedures (n=102), corresponding to 1 in 3030 women undergoing a peripartum hysterectomy and another 1 in 3030 women being managed by IR, thereby preserving the uterus. Seventeen women underwent hysterectomy following IR and three women needed further IR despite hysterectomy. Abnormal placentation and/or uterine atony were the reported causes of haemorrhage in 83.7%. Abnormally invasive placenta was not detected antenatally in 34% of cases. The interventions were planned in 15 women. Three women were transferred antenatally and 17 women postnatally to a hospital with emergency IR service. Urgent peripartum hysterectomy was averted in 72% of the women who were transferred, with no significant difference in need for transfusion. IR procedures were able to stop the bleeding in 87.8% of the attempts. Disseminated intravascular coagulation secondary to major haemorrhage was reported in 32 women (19%). Conclusion: The prevalence in Belgium of major obstetric haemorrhage requiring peripartum hysterectomy and/or IR is estimated at 6.6 (95% CI 5.7 to 7.7) per 10 000 deliveries. Increased clinician awareness of the risk factors of abnormal placentation could further improve the management and outcome of major obstetric haemorrhage. A case-by-case in-depth analysis is necessary to reveal whether the hysterectomies and arterial embolisations performed in this study were appropriate or preventable.